Effects of amodiaquine on Brugia pahangi infection in Aedes togoi - Sugeng Juwono Mardihusodo., Sugeng Juwono Mardihusodo. (Universitas Gadjah Mada, 1987)
A primary screening of amodiaquine as a filaricide using Brugia pahangi .Aedes togoi model infection was carried out. The drug dissolved in 10% sucrose water solution in the concentrations of 100 mg%, 200 mg% and 400 mg% fed ad libitum to the uninfected and infected mosquitoes for 4, 8 and 12 days showed definite insecticidal and filaricidal activities. Key words: primary filaricide screening - amodiaquine - Brugia pahangi - Aedes togoi model infection - filariasis - parasitology